Effect of submarine groundwater discharge on the coastal ocean inorganic carbon cycle. (3rd August 2014) - Liu, Qian; Charette, Matthew A.; Henderson, Paul B.; McCorkle, Daniel C.; Martin, William; Dai, Minhan
Abstract : Using radium (Ra) isotopes, we estimate that the average submarine groundwater discharge (SGD) flux (marine plus terrestrial groundwater) into the southwest Florida Shelf (SWFS) was 20 ± 10 × 10 7 and 18 ± 8 × 10 7  m 3  d −1 in July and October 2009, respectively. The terrestrial groundwater flux was the same order of magnitude as the local river discharge in July 2009. Shelf‐water total alkalinity (TAlk) and dissolved inorganic carbon (DIC) concentrations could not be explained by river inputs alone, suggesting a groundwater source. We estimated SGD fluxes of TAlk and DIC using the SGD flux derived from a shelf‐water 226 Ra budget and TAlk and DIC concentration differences between the groundwater and seawater. These fluxes were also determined by the observed TAlk : 226 Ra and DIC : 226 Ra relationships in the shelf water, and the 226 Ra flux sustained by SGD. These TAlk and DIC fluxes were 11–71 times more than the combined input of local rivers, suggesting that SGD was the dominant source of TAlk and DIC to the SWFS during 2009. SGD is an important component of the inorganic carbon budget for the coastal ocean.